Penggunaan Cerita Rakyat Sebagai Media Pembelajaran Untuk Menumbuhkan Pemahaman Membaca Siswa Sekolah Dasar - Nisdayanti Nisdayanti (Prodi PGSD Unsultra, 2023)
This study aims to analyze the role of folklore as a learning medium in improving elementary school students' reading comprehension. Folklore, as a cultural heritage rich in moral values, can be used to stimulate reading interest, enrich vocabulary, and improve students' analytical skills. This literature study examines various relevant previous studies. The results of the study indicate that the use of folklore is effective in creating interactive and meaningful learning. This article recommends the integration of folklore into the Indonesian language learning curriculum in elementary schools